P–667 Dydrogesterone supplementation in cycles triggered with lone GnRH agonist for final oocyte maturation resulted in an acceptable pregnancy rate. (6th August 2021) - Safrai, M; Hertsberg, S; Meir, A Be; Reubinoff, B; Imbar, T; Mordechai-Daniel, T; Simon, A
Abstract: Study question: Can luteal oral Dydrogesterone (Duphaston) supplementation in an antagonist cycle after a lone GnRH agonist trigger rescue the luteal phase, allowing the possibility to peruse with fresh embryo transfer? Summary answer: Functionality of the luteal phase in an antagonist cycle after a lone GnRH agonist trigger can be restored by adding Duphaston to conventional luteal support. What is known already: Ovarian hyperstimulation syndrome (OHSS) is dramatically reduced when using antagonist cycle with lone GnRH agonist trigger before ovum pick up. This trigger induces short luteinizing hormone (LH) and follicle-stimulating hormone (FSH) peaks, associated with reduced progesterone and estrogen levels during the luteal phase. They cause an inadequate luteal phase and a significantly reduced implantation rate leading to a freeze all practice in those cycles. Study design, size, duration: A retrospective cohort study. The study group (n = 123) included women that underwent in vitro fertilization cycles from January 2017 to May 2020. Patients received a GnRH-antagonist with a lone GnRH-agonist trigger due to imminent OSHH. The control group (n = 374) included patients under 35 years old that, during the same time period, underwent a standard antagonist protocol with a dual trigger of a GnRH-agonist and hCG. Participants/materials, setting, methods: Study patients were given Dydrogesterone (Duphaston) in addition to micronized progesterone vaginal pills (Utrogestan) for luteal support (Duphaston group). Controls were treated conventionally with Utrogestan for luteal phase support (hCG group). The outcomes measured were pregnancy rate and OHSS events. Main results and the role of chance: Our study was the first to evaluate the addition of Duphaston to standard luteal phase support in an antagonist cycle triggered by a lone GnRH agonist before a fresh embryo transfer. The mean number of oocytes retrieved and estradiol plasma levels were significantly higher in the Duphaston group than in the hCG group (16.9 ±7.7 vs. 10.8 ± 5.3 and 11658 ± 5280 pmol/L vs. 6048 ± 3059 pmol/L, respectively). The fertilization rate was comparable between the two groups. The mean number of embryos transferred and the clinical pregnancy rate were also comparable between groups (1.5 ± 0.6 vs 1.5 ± 0.5 and 46.3% vs 40.9%, respectively). No OHSS event was reported in either group. Limitations, reasons for caution: This retrospective study may carry an inherent selection and information bias, derived from medical record coding. An additional limitation was the choice of physician for the lone GnRH trigger, which may have introduced a selection bias and another potential caveat was the relatively small sample size of our study groups. Wider implications of the findings: The addition of Duphaston to conventional luteal support could effectively salvage the luteal phase without increasing the risk for OHSS. This enables, to peruse in those cycle, with fresh embryo transfer, avoiding the need to freeze all the embryos and postponed embryo transfer. Leading to lower psychological burden and costs. Trial registration number: 0632–20-HMO